Perbedaan Perkembangan Motorik Halus Anak Usia 48-60 Bulan yang diberi Permainan Kinetic Sand di TK Islam Terpadu Al-Azhar Kabupaten Jember - Fadilah, Alnalia; Palupi, Jenie; Kiswati, Kiswati (Jember Maternal and Child Health Journal, 2024)
Fine motor skills are an important aspect in the development of preschool children. The main cause is because parents do not provide enough stimulation to their children. One activity that can influence aspects of a child's fine motor development is using kinetic sand as a playing medium. Based on data from UNICEF (United Nations Emergency Children's Fund) in 2019, it was reported that the prevalence of children under five years of age experiencing growth and development disorders was 28.7% and Indonesia was the third country with the highest prevalence in the Southeast Asia Region. East Java Province has a prevalence rate of fine motor development disorders in early childhood of 24.5%. The research design used a quasi experimental approach with a post-test only control design. The population was 35 children with a sample size of 32 children taken using simple random sampling techniques. Data collection was obtained from observations based on the checklist instrument. Data analysis using the Simple Paired T Test. The results of the research show that the p value (0.001) or p-value < ? 0.05 so H0 is rejected, meaning that there is a difference in the fine motor development of children aged 48-60 months who were given the kinetic sand game at the Al Azhar Integrated Islamic Kindergarten, Jember Regency, so it is hoped that teachers and parents always provide and train their children's fine motor skills, one of which is using various types of educational games